(untitled) (Fiep Bulletin - online, 2024)
Auriculotherapy is a technique of Traditional Chinese Medicine that is well-known in the West. It involves the application of mustard seeds or needles on energy channel points to promote harmonization. This technique is widely accepted by patients as it is non-invasive and quick to administer. The present study aimed to assess the applicability of this protocol and its benefits for adapted canoeing athletes. Three paracanoe athletes were recruited and subjected to auricular therapy, focusing on three points: SHEM MEN, RIM, and SYMPATHETIC NERVES. Data collection involved word cloud surveys at the end of the week. According to the patients’ perspective, the protocol led to improvements, especially in sleep quality and overall energy levels, which were mentioned over the course of three weeks during training sessions. In conclusion, auriculotherapy proved to be an effective resource for enhancing athletes’ energy levels, sleep quality, and overall well-being. However, further studies with larger samples are needed to delve deeper into its therapeutic potential.